Integrasi Pendidikan Qur’ani dan Neurosains dalam Meningkatkan Kecerdasan Anak Usia Dini - Latifah, Aeni; Sahroni, Dadang; Hilman, Cecep; Afriliani, Ajeng Teni Nur; Sarmita, Sarmita (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyse the concept of integrating Qur’anic education and neuroscience in enhancing early childhood intelligence and to identify its implications for effective learning strategies. This research employs a qualitative approach using a library research method by examining various relevant scientific literatures. The data used are secondary data obtained from books, scholarly journal articles, and academic documents related to Qur’anic education, neuroscience, and early childhood development. Data were collected through documentation study by exploring, reviewing, and analysing relevant literature sources. The data were then analysed using a descriptive-analytical method through processes of classification, interpretation, and synthesis of the identified concepts. The findings indicate that Qur’anic education plays a significant role in shaping the balance of children’s intellectual, emotional, and spiritual intelligence, while neuroscience provides scientific insights into brain development processes and optimal strategies for stimulating children's cognitive potential. The integration of these two approaches can enhance memory, concentration, and children's critical and creative thinking skills through learning methods aligned with the stages of brain development. Therefore, this integrative approach has the potential to improve the quality of early childhood education holistically and can serve as a reference for developing curricula and learning strategies that are more effective and applicable.